Assessment of Concrete Bridges : Models and Tests for Refined Capacity Estimates - Bagge, Niklas (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2014)
Optimising the strategy for repairing, upgrading and replacing bridges in the European Union, and elsewhere, is becoming increasingly important due to ageing of the bridge stock, continuously increasing load requirements and budgetary limitations. Thus, there is a clear need to identify or develop, and implement, refined methods for assessing existing bridges in order to determine the most cost-effective options and actions to extend their lives, increase their capacities or replace them.Thus, the objective of the research project partly reported in this licentiate thesis is to verify and calibrate methods for refined assessment of existing bridges, using information acquired in an extensive program of experimental studies. In addition to describing parts of the project, the thesis is intended to provide a basis for suggestions and a discussion of the author’s future research in the area. It includes presentations of two experimental studies designed to evaluate, and calibrate, assessment methods:1. A laboratory-based experimental study of 12 two-span continuous reinforced concrete beams conducted in Dublin, Ireland, in 2012. The tests particularly focused on the beams’ nonlinear overall behaviour and related redistribution of internal forces.2. A full-scale test of a 55 year-old post-tensioned girder bridge in Kiruna, Sweden, in 2014, focusing on: (a) failure loading of the main girders, (b) failure loading of the slab, (c) the condition of post-tension cables, and (d) two strengthening systems using carbon fibre reinforced polymers (CFRP).The continuous reinforced concrete beams behaved in a nonlinear manner from an early stage in the loading. This is not usually considered in either the design or assessment of existing bridges, but should be for the verification to be accurate at the serviceability and ultimate limit states (SLS and ULS, respectively). The results also indicated that there was more redistribution of internal forces at the ULS than stated in standards. Thus, use of refined methods to assess ...